Integração da saúde mental com a intenção primária em saúde: estudo de caso etnográfico no município de Ipatinga-MG - Maria Aline Gomes Barbosa (2009)
This paper is a report on the construction of perceptions and practices in mental health of workers by the Primary Healthcare (APS) - members of teams in the family health and mental health - produced through ethnographic case study conducted within the health system of the City of Ipatinga - MG. This research involved the insertion of the researcher in the field, also employed by the City Mental Health Program. We aim to get into the challenges of Psychiatric reform in its daily life, from a singular example of the changes in mental health, with an eye for detail and privileged to unroll the process. The existence of a large group of psychology professionals in the health system of this city contributed significantly to the production of actions to the mental health in the Primary Healthcare (APS), which allowed the construction of a non-medical local reference to that type of attention. The events of Ipatinga is a process full of contradictions, but also to "test", whichshows the important openings for experimentation, which is characteristic in the field of public health and mental health. One of the main contributions from the experience of this research is the fact that the integration of mental health in the APS is a constant challenge linked by historical conditions, ideological and political systems of local health and the involvement of its parties. This challenge points out to the construction of a health care network within SUS that should not only come from a service - the APS or Center for Psychosocial Care, for example - because this service will eventually become a central hub as has happened to the service of the Primary Healthcare Unit of Ipatinga. The proposed network is more likely to be a polyarchal organization where local services can be increasingly open to any territory, and less of a hierarchical network in which the services are closed within themselves.